The Influence of Food and Con-specifics on the Flight Potential of the Parasitoid Ibalia leucospoides - Fischbein, Deborah (2011)
For insect parasitoids, knowledge of their flight capability is essential for a general understanding of the relationship with their hosts. For instance, flight capacity might partly determine their efficacy as biological control agents. Ibalia leucospoides Hochenwarch (Hymenoptera: Ibaliidae) is a solitary, pro-ovigenic parasitoid of the woodwasp, Sirex noctilio Boidin (Hymenoptera, Siricidae), an economically important pest of softwood forestation. This study explores the flight capacities of I. leucospoides females and assesses the effects of a sugar-rich food supply and crowding on female flight performance, by using computer-linked flight mills. The present study shows: (1) a high variability in flight potential of I. leucospoides females, (2) no effects of food supply and grouping on wasp flight (flight distance and speed), (3) a significant effect of body size and wing loading on flight performance and, (4) a significant body mass loss during the flight dependent on the total distance flown. The lack of effect of food on a highly energy-demanding activity as flight may be related to the life-history traits and nutritional strategies of this parasitoid. The relevance of these observations for the use of I. leucospoides as a biological control agent is discussed.